O lugar que ainda não existe no mapa: a reconstrução da América Latina em Días y noches de amor y de guerra, de Eduardo Galeano - Felipe Roner Vilanova Novais (2023)
The purpose of this research is to investigate the work of the Uruguayan writer Eduardo Galeano Días y noches de amor y de Guerra. To such end, the author’s work will be analyzed primarily through the lens of Aleida Assmann, Tzvetan Todorov, Elizabeth Jelin and Walter Benjamin. Understood in its power, Galeano's exemplary use of memory will be examined, highlighting the metaphors of remembrance that take shape in his text. In addition, the work articulates such reflections with the conceptions about testimony taken up by Márcio Seligmann-Silva, João Camillo Penna, and Giorgio Agamben, considering their articulation with reality and the ways in which the testimonial subjects appear in the text. Finally, an exegesis is carried out in terms of a literary cartography that takes form within the work, in which a version of Latin America is glimpsed from memories outside the scope of official reports and multiplied in the form of the chronicle. Therefore, discussions in the field of geography that think of Latin America as a territory – traversed by power – are sought, particularly through the works of Marcos Aurelio Saquet and Marcelo José Lopes Souza. The image returned to the Latin American continent, a process designed based on Didi-Huberman’s discussions, holds, simultaneously, a commitment to the past and a desire for a future that is concerned with not repeating episodes of violence.